Ecological basis of development of meadow ecosystems in the valley of the Southern Canal of the Obra River = Ekologiczne podstawy wykształcania ekosystemów łąkowych w dolinie Kanału Południowego Obry - Klarzyńska, Agnieszka; Kryszak, Anna; Kryszak, Jan; Musiał, Maciej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the course of long-term studies, the impact of site conditions ? mois-ture condition and trophic factors ? on meadow plant communities was assessed by determining their physiological structure and Shannon-Wiener floristic diversity index ? H?. The obtained results were compared with the site and floristic investigations from 1994. In the case of the Obra River valley, it was moisture level and nitrogen content in the soil that exerted the most important influence on the development of meadow communities as indicated by the occurrence of unstable transitory forms. They differ from one another with regard to floristic diversity and a small proportion of characteristic species. Utilisation and its intensity, alongside site conditions, exert a modifying influence on the floristic composition of communities allowing random species to settle among them and to reduce their stability.
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); meadows community; the Obra River Southern Canal valley; site; ecological factors; floristic diversity; zbiorowiska łąkowe; dolina Kanału Południowego Obry; siedlisko; czynniki ekologiczne; zróżnicowanie florystyczne